2022
DOI: 10.1172/jci152418
|View full text |Cite
|
Sign up to set email alerts
|

CD69 expression on regulatory T cells protects from immune damage after myocardial infarction

Abstract: Increasing evidences advocate for an important function of T cells in controlling immune homeostasis and pathogenesis after myocardial infarction (MI), although the underlying molecular mechanisms remain elusive. In this study, a broad analysis of immune markers in 283 patients revealed a significant CD69 overexpression on Treg cells after MI. Our results in mice showed that CD69 expression on Treg cells increased survival after left-anterior-descending coronary artery (LAD)-ligation. Cd69 -/mice developed str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…32 Our findings are in line with a recent publication by Blanco-Domínguez reporting that CD69 expressing Tregs led to an improved outcome in experimental MI model by suppressing IL-17 production. 6 Moreover, the group has shown that increased expression of CD69 on peripheral blood cells after MI in humans was associated to lower-risk rehospitalization due to heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Our findings are in line with a recent publication by Blanco-Domínguez reporting that CD69 expressing Tregs led to an improved outcome in experimental MI model by suppressing IL-17 production. 6 Moreover, the group has shown that increased expression of CD69 on peripheral blood cells after MI in humans was associated to lower-risk rehospitalization due to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies by our group and others demonstrated that CD4 + T cells, particularly Tregs expressing the transcription factor FOXP3 (Forkhead box P3), can foster myocardial healing. [3][4][5][6][7] Increased T cell signal was observed in heart-draining lymph nodes of infarcted patients and Tregs are present in cardiac biopsies, 7 suggesting those responses are conserved in humans. Yet, chronic T cell activation has been shown to mediate detrimental remodeling during both pressure overload and aging.…”
Section: Original Researchmentioning
confidence: 99%
“…Studies have shown that IL-17A secreted by Tgd cells can induce cardiomyocyte apoptosis 41 . By regulating the IL-17A/Tgd cells axis, it can effectively regulate the level of inflammation and slow down the process of myocardial fibrosis 42 , 43 . The enrichment of Neurons in heart failure samples may be related to the increase of cardiac sympathetic nerve activity and the enhancement of N-type Ca 2 + currents 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Infarcted hearts with infiltration of CD4(+)Foxp3(+)CD73(+) regulatory T cell help prevent adverse ventricular remodeling and improve cardiac function after MI by inhibiting inflammation and directly protecting cardiomyocytes ( 54 , 61 ). In addition, studies have shown that Treg cells reduce the recruitment of IL-17+γδT cell and increase survival in mice with MI ( 62 ). CXCR4 antagonist POL5551 attenuated inflammatory gene expression in monocytes and macrophages by enhancing the action of Treg cells and attenuated left ventricular remodeling and systolic dysfunction, suggesting that enhancing Treg cell expression is important for restoring myocardial function ( 63 , 64 ).…”
Section: Immune Cellmentioning
confidence: 99%